2021
DOI: 10.3332/ecancer.2021.1225
|View full text |Cite
|
Sign up to set email alerts
|

The determinants of knowledge of cervical cancer, attitude towards screening and practice of cervical cancer prevention amongst antenatal attendees in Ibadan, Southwest Nigeria

Abstract: Cervical cancer (CC) is an extremely preventable and curable disease with early detection and treatment. Unfortunately, the practice of cervical cancer prevention (CCP) remains poor in resource constrained countries. This study aimed to identify determinants of knowledge of CC, attitude towards cervical cancer screening (CCS) and practice of CCP among antenatal attendees in a tertiary hospital in Southwest Nigeria as they are sexually active women. This was a cross-sectional survey of a cohort of 287 antenatal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 26 publications
0
12
1
Order By: Relevance
“…A study in Lagos [14], reported very low belief in personal susceptibility to cervical cancer as none of the women felt they were at risk of cervical cancer, even though 73.3% were inclined to be tested for cervical cancer. From a study by Agboola and Bello [20] only 16.7% of the women reported that they were susceptible to cervical cancer. This finding was also observed among health workers in Benin City in Nigeria where up to 89% of female health workers surveyed felt they were not at risk of developing cervical cancer [39].…”
Section: Cervical Cancer Attitudementioning
confidence: 98%
See 2 more Smart Citations
“…A study in Lagos [14], reported very low belief in personal susceptibility to cervical cancer as none of the women felt they were at risk of cervical cancer, even though 73.3% were inclined to be tested for cervical cancer. From a study by Agboola and Bello [20] only 16.7% of the women reported that they were susceptible to cervical cancer. This finding was also observed among health workers in Benin City in Nigeria where up to 89% of female health workers surveyed felt they were not at risk of developing cervical cancer [39].…”
Section: Cervical Cancer Attitudementioning
confidence: 98%
“…In contrast, in a study among female health care workers in Enugu, about half of the respondents with adolescent daughters had immunized their daughters [19]. Some reported barriers to uptake of cervical cancer screening services include fear of a positive cervical cancer diagnosis, and other fears related to the screening procedures and vaginal examinations [20].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Cervical cancer is one of the major noncommunicable public health problems among women globally and is an extremely preventable and curable disease with early detection and treatment. 1,2 Approximately half a million women develop cervical cancer each year, with an estimated 85% or more occurs in developing countries, including Ethiopia. 2,3…”
Section: Introductionmentioning
confidence: 99%
“…Cervical cancer is one of the major noncommunicable public health problems among women globally and is an extremely preventable and curable disease with early detection and treatment. 1,2 Approximately half a million women develop cervical cancer each year, with an estimated 85% or more occurs in developing countries, including Ethiopia. 2,3 Cervical cancer is mainly preventable ensuring the introduction of effective cervical cancer screening, providing vaccination, early detection, and reducing cervical cancer.…”
Section: Introductionmentioning
confidence: 99%